Pierwsze reakcje dyplomacji czechosłowackiej na projekt zachodnioeuropejskiego paktu bezpieczeństwa w 1925 roku - Nowinowski, Sławomir M. (Acta Universitatis Lodziensis. Folia Historica, 2002)
The memorandum of the German Government wich was proposed to France on 9 February 1925 was the turning point of the safety negotations concerning the collective security in Europe. The project of the Rhine Pact was a real menance to the collapse of the collective security in Europe, and Eduard Benes’s foreign policy he had been doing so far. The diplomacy of the Czechoslovakia took energetic decisions to reduce the menace. However, its activities were characterized with a great diplomacy and even willing to compromise. In the first stage of negatiations BeneS behavied as if he didn’t realise the radically change of the situations in Europe, and tried to support the optimal project, from his point of view, wich refered to Geneva Protocol. BeneS was aware of leading the offer of the German Government to the issue of arbitration only. He stressed that striving for standardization of the relations with Germany couldn’t be treted by Paris as the pretext for withdrawing from the alisation o f French-Brilish Pact. During the XXXII session of the Council the League of Nations in March 1925 he realized however what the new settlement of armed forces on the continent was to be based on. He refused the possibility of contestation and followed the trac marked out by the great powers. Keeping distance from Poland he was looking for agreement with Germany on his own trying to do his best in gaining as many benefits for his country as possible which he treated as imminent.